Bromatological, microbiological, and effectiveness evaluation of gummies fortified with vegetable extract and bovine blood meal - Díaz LLocclla, Marianela (2026)
Iron deficiency anemia in children remains a public health problem of concern, especially in rural areas of Peru. The objective of this study was to evaluate the bromatological, and microbiological composition and efficacy of gummies fortified with carrot extract (M1), beet extract (M2), and bovine blood meal. A sample of 20 school-age children from the district of Los Morochucos was divided into two groups, one for M1 and the other for M2. Both gummy formulations showed acceptable levels of moisture, potassium, iron, and nitrogen, low levels of copper, arsenic, and lead, and microbiological parameters indicated that the gummies were safe for human consumption. In terms of efficiency, M2 was better, increasing hemoglobin levels from 12.12 to 12.63 g/dL, which is attributed to the synergy that develops between iron and beet compounds that promote its absorption. In contrast, gummies fortified with carrot extract showed no significant changes, which could be associated with low compliance in accompanying gummy consumption with a citrus drink, which in turn influenced the bioavailability of iron. The results show that it is possible to include gummies fortified with vegetable extracts and bovine blood meal as part of the diet of school-age children who are vulnerable to anemia.